2022
DOI: 10.5540/03.2022.009.01.0311
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-based Dengue Outbreaks Modelling with Exogenous Variables

Abstract: Dengue fever is an endemic disease, present in tropical and subtropical regions, transmitted by the Aedes Aegypti mosquito vector. It has recently appeared in non-tropical regions with dry weather. This represents a setback for advanced temperature-based reference models, since mosquitos reproductive cycle does not necessarily match with the outbreaks. This situation indicates that other variables are also involved in epidemic outbreaks. In this work we propose to include a component that capture this process,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…To capture this phenomenon, we considered the effects of weather on the transmission rate by replacing the constants x 1 and x 2 with a time-dependent variable b ex 2 R resulting from a Gaussian function. The Gaussian function is defined as [14] b ex ≔k e À ðx À uÞ 2 2s 2 ; ð11Þ…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations
“…To capture this phenomenon, we considered the effects of weather on the transmission rate by replacing the constants x 1 and x 2 with a time-dependent variable b ex 2 R resulting from a Gaussian function. The Gaussian function is defined as [14] b ex ≔k e À ðx À uÞ 2 2s 2 ; ð11Þ…”
Section: Plos Onementioning
confidence: 99%
“…There was a strong correlation between the temperature and bb v , but β ex was needed to adjust β hv (similar results were obtained for β vh ). The importance of considering the modulation is relevant because several studies have reported that the climate-based variables determine the prediction and fitting of the SIR-SI model [14,18,24]. It is important to note that the climate of Lima is characterized by low levels of rainfall and variable temperature according to region owing to the effects of the ocean and the Andes Mountains.…”
Section: Behavior Of the Infection Rate βmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of data and model tuning approaches were also identified. For example, some studies utilized synthetic rather than real data (Bogado et al., 2020 ; Kinney et al., 2021 ). Another study that applied a fully‐connected artificial neural network to predict mosquito abundance in urban areas of South Korea varied the learning rate and number of neurons in the hidden layer to find the model with minimum mean square error (Lee et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%